2018 55th ACM/ESDA/IEEE Design Automation Conference (DAC) 2018
DOI: 10.1109/dac.2018.8465575
|View full text |Cite
|
Sign up to set email alerts
|

Response-Time Analysis of DAG Tasks Supporting Heterogeneous Computing

Abstract: Hardware platforms are evolving towards parallel and heterogeneous architectures to overcome the increasing necessity of more performance in the real-time domain. Parallel programming models are fundamental to exploit the performance capabilities of these architectures. This paper proposes a novel response time analysis (RTA) for verifying the schedulability of DAG tasks supporting heterogeneous computing. It analyzes the impact of executing part of the DAG in the accelerator device. As a result, the response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…The work in [36] proposes a mapping of multiple DAG tasks that also minimizes power consumption, without considering hardware accelerators. A response time analysis for a DAG task on a heterogeneous platform with a single hardware accelerator is presented in [66]. Only applications performing a single acceleration request for the whole application (composed of a single DAG task) are supported.…”
Section: Related Workmentioning
confidence: 99%
“…The work in [36] proposes a mapping of multiple DAG tasks that also minimizes power consumption, without considering hardware accelerators. A response time analysis for a DAG task on a heterogeneous platform with a single hardware accelerator is presented in [66]. Only applications performing a single acceleration request for the whole application (composed of a single DAG task) are supported.…”
Section: Related Workmentioning
confidence: 99%
“…The algorithm does not consider the task execution interval defined by the parallel node segment, which will cause a large number of processors to be idle waiting for the execution of other task nodes in the same node segment, and the WCRT obtained is less accurate. Serrano et al [13] proposed a DAG conversion strategy for DAG tasks that support parallel and heterogeneous computing. This strategy avoids the interference between parallel tasks by allocating some of them to the accelerator for execution, reduces the idle waiting time of the processor, and obtains the WCRT of the task, but this method does not consider the possibility that the assignment of different tasks leads to different results.…”
Section: A Polynomial Calculationmentioning
confidence: 99%
“…Previous studies [10][11][12][13] analyzed the execution sequence of the tasks, studied the relationship among the execution time of tasks, the length of the critical path, and the WCRT, and helped improve the effect of the task execution time on the WCRT for polynomial solving tasks. Using polynomial needs to consider the influence of different factors on the WCRT, and the calculation method is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…AMPERE's vision is that state-of-the-art parallel programming execution models are mature enough (or can be efficiently extended) to support the fulfillment of functional and non-functional constraints captured by the DSML used to develop CPSs. Interestingly, despite current parallel programming models are agnostic of non-functional constraints, recent studies demonstrated that OpenMP allows providing trustworthy timing guarantees [24]- [28], and so fitting the timing requirements of critical systems. Moreover, it has been demonstrated that OpenMP is not a threat regarding functional safety [29], and that both compilers and runtimes can be used to check correctness and recover from failures [21].…”
Section: B the Ampere Software Architecturementioning
confidence: 99%